YouTubers as satirists: humour and remix in online video - Silva, Patrícia Dias da (2012)
This article aims to discuss the role humour plays in politics, particularly in a media environment overflowing with user-generated video. We start with a genealogy of political satire, from classical to Internet times, followed by a general description of “the Downfall meme,” a series of videos on YouTube featuring footage from the film Der Untergang and nonsensical subtitles. Amid video-games, celebrities, and the Internet itself, politicians and politics are the target of such twenty-first century caricatures. By analysing these videos we hope to elucidate how the manipulation of images is embedded in everyday practices and may be of political consequence, namely by deflating politicians' constructed media image. The realm of image, at the centre of the Internet's technological culture, is connected with decisive aspects of today's social structure of knowledge and play. It is timely to understand which part of “playing” is in fact an expressive practice with political significance.